Role of Proton Beam Therapy in Spinal Chordomas: A Narrative Review of The Literature - Syed Faisal Nadeem; Ahsan Ali Khan; Muhammad Shahzad Shamim (Journal of the Pakistan Medical Association, 2024)
Chordomas are rare malignant neoplasms arising from vestigial remnants of the embryonic notochord. Approximately 55-70% of chordomas develop within the vertebral column. Their affinity to develop within the bones of the axial skeleton and propensity to locally invade and recur makes them challenging candidates for complete surgical excision. Adjuvant therapies are hence necessary to improve outcomes; for which chemotherapy has been observed to be largely ineffective, owing to the tumour being resistant to it. Radiotherapy is the current adjuvant therapy of choice for chordoma management. Over the years, proton beam therapy (PBT) has been the subject of medical attention, given the dosimetric benefits it confers over traditional radiotherapy, allowing more concentrated radiation to be given to the target of interest and reducing damage to surrounding normal tissue. A review of the current literature reveals PBT offers significantly better outcomes when used as an adjuvant to maximal surgical resection rather than as a definitive therapy. Keywords: Chordoma, Proton Beam Therapy, Outcome, Recurrence, Spinal, Adjuvant Therapy